Method for analyzing adsorption efficiency of dispersing agent in oily color paste
The difference in weight loss rate between pigments and dispersants in color pastes was analyzed by thermogravimetric analysis, which solved the gap in the study of dispersant adsorption efficiency in color pastes, and achieved simple and effective quantitative analysis, supporting color pastes in coatings, inks, plastics, etc. performance regulation and application development in the field.
Patent Information
- Application Number
- CN202411094311.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art lacks a simple and effective method to quantitatively analyze the adsorption efficiency of dispersants in color pastes, affecting the rheological conditions and paint film performance of coating construction applications.
Thermogravimetric analysis method is used to quantitatively analyze the adsorption efficiency of dispersant on the pigment surface of the pigment in the color paste by using the thermogravimetric analysis method. It is simple to operate and does not require complex sample pretreatment, and is suitable for oil properties. and water-based color paste.
It provides theoretical guidance for color paste formula design and performance regulation, reduces the cost of the instrument, and is widely used in applications in coatings, inks, plastics, cosmetics and other fields.
Smart Images

Figure CN119198428A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of color paste analysis, and mainly to an analysis method for the adsorption efficiency of a dispersant in an oily color paste. Background Art
[0002] In the fields of coatings, inks, plastics, cosmetics, etc., color pastes are important colorants and functional materials. The pigment dispersion of the color paste itself has a vital impact on the appearance and performance of the terminal application products, and the dispersion of the color paste is largely determined by the performance of the dispersant. Dispersants are adsorbed on the surface of the pigment, providing steric effect or charge effect to make the pigment particles repel each other, blocking the aggregation and flocculation between the pigment particles due to the van der Waals force, so that the pigment particles remain in a uniform and stable state in the dispersion medium, so that the color paste has excellent dispersion stability, rheological properties and color effects. However, in the color paste, not all dispersant molecules can be adsorbed on the surface of the pigment. There are still many dispersant molecules that are free in the color paste solvent. This part of the free dispersant will significantly affect the rheological conditions and paint film properties of the coating application, such as film adhesion, scratch resistance, high-pressure water wash resistance, adhesion and hardness. Therefore, the study of the adsorption efficiency of dispersants in color pastes is crucial for the formulation design and performance regulation of coatings, but there is currently a lack of a simple and effective method to quantitatively analyze the adsorption efficiency of dispersants in color pastes.
[0003] Thermogravimetric analysis (TGA) is a commonly used thermal analysis technique that can accurately measure the mass change of a sample under heating conditions and reveal the thermal decomposition weight loss process of the sample. By analyzing the weight loss steps and weight loss rates on the thermogravimetric curve, the content of each component in the sample, thermal stability, decomposition temperature range and other information can be analyzed. Since thermogravimetric analysis has the advantages of simple and fast operation and no need for complex sample pretreatment, it is widely used in the research of polymer materials, ceramics, biomass and other fields.
[0004] The present invention applies thermogravimetric analysis to the technical field of color paste analysis, and quantitatively analyzes the adsorption efficiency of the dispersant in the color paste on the pigment surface through the difference in weight loss rates of the pigment and the dispersant in the color paste in the thermogravimetric analysis test, thereby providing theoretical guidance and data support for the formulation design and performance regulation of the color paste, which is of great significance to the application and development of the color paste in the fields of coatings, inks, plastics, cosmetics, etc. Summary of the invention
[0005] Based on the above facts, the purpose of the present invention is to solve the deficiencies or gaps in the prior art, and to provide a method for analyzing the adsorption efficiency of dispersants in oily color pastes. More specifically, a method for quantitatively analyzing the adsorption efficiency of dispersants in oily color pastes using thermogravimetric analysis is provided. This method quantitatively analyzes the adsorption efficiency of dispersants on the surface of pigments in color pastes by the difference in weight loss rates of pigments and dispersants in oily color pastes in thermogravimetric analysis tests. It is simple to operate, does not require complex sample pretreatment processes, and has low instrument costs. It is also universal for water-based color pastes and resin-free color pastes, and can be widely used in the field of color paste analysis technology.
[0006] The method for analyzing the adsorption efficiency of the dispersant in the oily color paste of the present invention mainly comprises the following steps:
[0007] (1) drying the dispersant sample used in the oil-based color paste to remove the organic solvent and obtain a dispersant sample with 100% effective content;
[0008] (2) drying the pigment used in the oil-based color paste to remove the adsorbed solvent that may be contained therein to obtain a pigment sample with 100% effective content;
[0009] (3) centrifuging the oily color paste, collecting the obtained solid and dispersing and washing it with an organic solvent, centrifuging it again, collecting the obtained solid and drying it, removing the organic solvent to obtain a pigment sample with 100% effective content of the dispersant effectively adsorbed;
[0010] (4) performing thermogravimetric analysis on the 100% effective dispersant sample, the 100% effective pigment sample, and the 100% effective dispersant effectively adsorbed pigment sample to obtain thermogravimetric curves (TGA) of the three samples;
[0011] (5) performing first-order differential data processing on the thermogravimetric curves (TGA) of the 100% effective dispersant sample and the 100% effective pigment sample to obtain differential thermogravimetric curves (DTG) of the two samples;
[0012] (6) Comparing the differential thermogravimetric curves (DTG) of the 100% effective dispersant sample and the 100% effective pigment sample, determining the temperature at the intersection of the differential thermogravimetric curves of the 100% effective dispersant sample and the 100% effective pigment sample, and recording it as the adsorption efficiency analysis temperature (T A );
[0013] (7) The dispersant sample with 100% effective content, the pigment sample with 100% effective content, and the pigment sample with 100% effective content effectively adsorbed by the dispersant are subjected to an adsorption efficiency analysis temperature (T A ) are recorded as W D , WP and W P- D ;
[0014] (8) Using the three mass percentage data described in (7), calculate the proportion of dispersant in the pigment sample effectively adsorbed by the dispersant with 100% effective content, X. D and pigment ratio X P , the calculation formula is X D =(W P-D -W P )÷(W D -W P )×100%,X P =(1-X D )×100%;
[0015] (9) The percentage of dispersant in the pigment sample effectively adsorbed by the 100% effective dispersant described in (8) is X D and pigment ratio X P , calculate the dispersant adsorption efficiency E in the color paste, the calculation formula is E = (X D ×M P ) / (X P ×M D )×100%, where M P is the mass percentage of pigment in the oily color paste formula, and MD is the mass percentage of effective dispersant in the oily color paste formula.
[0016] Oily color paste
[0017] In some embodiments of the present invention, the oily color paste comprises, by weight percentage:
[0018]
[0019] The total mass percentage of the above components is 100%.
[0020] In some embodiments of the present invention, the method for preparing the oily color paste comprises the following steps:
[0021] (1) Mix the resin, dispersant and organic solvent according to the formula, stir at 800 r / min for 10 min, then add the pigment at the same stirring speed, stir at 1500 r / min for 30 min, and obtain a mixed solution A;
[0022] (2) Using a horizontal sand mill, using zirconium oxide beads as grinding media to grind and disperse the mixed solution A obtained in step (1), and maintaining the grinding state until the material fineness is dispersed to less than 5 μm, the oily color paste is obtained.
[0023] Preferably, the diameter of the zirconia beads in step (2) is in the range of 0.6-1.4 mm, and the filling rate is in the range of 70-85%.
[0024] 100% effective dispersant sample
[0025] In some embodiments of the present invention, the dispersant sample with 100% effective content is obtained by drying the dispersant sample in an oven at 120° C. for 24 hours. The purpose of this process is to remove the organic solvent in the dispersant.
[0026] 100% effective pigment sample
[0027] In some embodiments of the present invention, the pigment sample with 100% effective content is obtained by drying the pigment in an oven at 120° C. for 24 hours. The purpose of this process is to remove adsorbed solvents and adsorbed water that may be contained in the pigment production process.
[0028] 100% effective dispersant adsorbed pigment sample
[0029] In some embodiments of the present invention, the pigment sample with 100% effective dispersant adsorbed is prepared by the following steps:
[0030] (1) After the oily color paste sample is centrifuged at 15000 rpm for 30 min, the solid at the bottom is collected and dispersed and washed with an organic solvent;
[0031] (2) The washed sample was centrifuged again at 15,000 rpm for 30 min to remove the unabsorbed dispersant and resin remaining on the surface, and the solid at the bottom was collected;
[0032] (3) The collected solid is dried in an oven at 120° C. for 24 h to obtain a pigment sample in which 100% of the effective content of the dispersant is effectively adsorbed.
[0033] Thermogravimetric analysis test
[0034] In some embodiments of the present invention, the test conditions of the thermogravimetric analysis test are as follows:
[0035] (1) Protective gas: nitrogen or argon;
[0036] (2) Temperature range: 50℃-600℃ or 50℃-800℃;
[0037] (3) Heating rate: 10-30℃ / min;
[0038] (4) Test sample weight: 0.5-5.0 mg;
[0039] The beneficial effects of the present invention are as follows:
[0040] The present invention aims at the lack of research on the adsorption efficiency of dispersants in color pastes, and provides a quantitative analysis method for the adsorption efficiency of dispersants in oily color pastes. The analysis method quantitatively analyzes the adsorption efficiency of dispersants on the surface of pigments in the color pastes by the difference in weight loss rates between pigments and dispersants in the color pastes in thermogravimetric analysis tests. The method is simple to operate, does not require a complicated sample preparation process, has a low instrument cost, and is also universal for water-based color pastes and resin-free color pastes, and can be widely used in the field of color paste analysis technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The thermogravimetric curves (TGA) of the dispersant sample with 100% effective content and the phthalocyanine blue pigment sample with 100% effective content in the embodiment of the present invention are shown in FIG.
[0042] Figure 2 The differential thermogravimetric curves (DTG) of the dispersant sample with 100% effective content and the phthalocyanine blue pigment sample with 100% effective content in the embodiment of the present invention are shown in FIG.
[0043] Figure 3 Thermogravimetric curves (TGA) of phthalocyanine blue pigment sample A with 100% effective content of dispersant effectively adsorbed and phthalocyanine blue pigment sample B with 100% effective content of dispersant effectively adsorbed in the embodiment of the present invention. DETAILED DESCRIPTION
[0044] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with specific examples. It should be understood by those skilled in the art that the content specifically described below is illustrative and not restrictive, and should not be used to limit the scope of protection of the present invention. The raw materials and reagents used in the following examples are all products that can be purchased from conventional commercial channels unless otherwise specified.
[0045] Preparation of oily phthalocyanine blue paste
[0046] The oily phthalocyanine blue paste was prepared according to the recipe in Table 1 below.
[0047] Table 1 Formula of oily phthalocyanine blue paste
[0048]
[0049]
[0050] The preparation of the oily phthalocyanine blue slurry adopts a traditional sand grinding process, which includes the following steps:
[0051] (1) Mix the resin, dispersant and organic solvent according to the formula, stir at 800 r / min for 10 min, then add the pigment at the same stirring speed, stir at 1500 r / min for 30 min, and obtain a mixed solution A;
[0052] (2) Using a horizontal sand mill, grind and disperse the mixed solution A obtained in the above step using zirconium oxide beads as the grinding medium. The diameter of the zirconium oxide beads used for grinding and dispersion is 0.8-1.0 mm, and the filling rate is 75%; the grinding state is maintained until the fineness of the material is dispersed to 5 μm, and a sample is taken and recorded as phthalocyanine blue slurry sample A; the grinding is continued for 60 minutes, and the material is discharged and recorded as phthalocyanine blue slurry sample B.
[0053] Example: Analysis of the adsorption efficiency of dispersants in oily phthalocyanine blue slurry
[0054] (1) After centrifuging the phthalocyanine blue slurry sample A at 15000 rpm for 30 min, the bottom solid was collected and dispersed and washed with an organic solvent, and then centrifuged again at 15000 rpm for 30 min to remove the unabsorbed dispersant and resin remaining on the surface, and the bottom solid was collected and dried in an oven at 120° C. for 24 h to obtain the phthalocyanine blue pigment sample A with 100% effective content of the dispersant effectively adsorbed;
[0055] (2) After centrifuging the phthalocyanine blue slurry sample B at 15,000 rpm for 30 min, the solid at the bottom was collected and dispersed and washed with an organic solvent, and then centrifuged again at 15,000 rpm for 30 min to remove the unabsorbed dispersant and resin remaining on the surface, and the solid at the bottom was collected and dried in an oven at 120° C. for 24 h to obtain a phthalocyanine blue pigment sample B with 100% effective content of the dispersant effectively adsorbed;
[0056] (3) The dispersant sample used in Table 1 was dried in an oven at 120° C. for 24 h to obtain a dispersant sample with 100% effective content;
[0057] (4) The phthalocyanine blue pigment sample used in Table 1 was dried in an oven at 120° C. for 24 h to obtain a phthalocyanine blue pigment sample with 100% effective content;
[0058] (5) The above 100% effective dispersant sample, 100% effective phthalocyanine blue pigment sample, 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample A, and 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample B were subjected to thermogravimetric analysis tests respectively, with nitrogen as the protective gas, the temperature range being 50°C-600°C, the heating rate being 20°C / min, and the test sample weight being 1.0±0.2 mg. The weight loss data of the samples were automatically collected and recorded by the instrument, and the thermogravimetric curves (TGA) of the above 100% effective dispersant sample, 100% effective phthalocyanine blue pigment sample, 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample A, and 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample B were obtained respectively. The thermogravimetric curves are as follows: Figure 1 and Figure 3 As shown;
[0059] (6) The thermogravimetric curves (TGA) of the above 100% effective dispersant sample and 100% effective phthalocyanine blue pigment sample are subjected to first-order differential data processing to obtain the differential thermogravimetric curves (DTG) of the 100% effective dispersant sample and 100% effective phthalocyanine blue pigment sample (such as Figure 2 The temperature at the intersection of the differential thermogravimetric curves of the 100% effective dispersant sample and the 100% effective phthalocyanine blue pigment sample is selected as the adsorption efficiency analysis temperature (T A ), T A =465℃;
[0060] (7) The mass percentages of the 100% effective dispersant sample, the 100% effective phthalocyanine blue pigment sample, the 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample A, and the 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample B at the adsorption efficiency analysis temperature of 465° C. are respectively recorded as W D , W P , W P-D-A and W P-D-B From the thermogravimetric curves (TGA) of the above four samples, W D =9.67%, W P =96.53%, W P-D-A =85.61%, W P-D-B =84.43%;
[0061] (8) Based on the mass percentages of the above 100% effective dispersant sample, 100% effective phthalocyanine blue pigment sample, 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample A, and 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample B at the adsorption efficiency analysis temperature of 465°C, the dispersant ratio in the 100% effective dispersant effectively adsorbed phthalocyanine blue pigment sample A is calculated by the formula: D-A and pigment ratio X P-A , the calculation formula is X D-A =(W P-D-A -W P )÷(W D -W P )×100%=(85.61%-96.53%)÷(9.67%-96.53%)×100%=12.57%, X P-A =(1-X D-A )×100%=87.43%; by the same method, the proportion of dispersant effectively adsorbed by 100% effective dispersant in phthalocyanine blue pigment sample B is calculated as X D-B and pigment ratio X P-B , the calculation formula is X D-B =(WP-D-B -W P )÷(W D -W P )×100%=(84.43%-96.53%)÷(9.67%-96.53%)×100%=13.93%, X P-B =(1-X D-B )×100%=86.07%;
[0062] (9) The proportion of dispersant in the phthalocyanine blue pigment sample A effectively adsorbed by the 100% effective dispersant described in (8) is X D-A and pigment ratio X P-A Calculation of dispersant adsorption efficiency E in color paste A , the calculation formula is E A =(X D-A ×M P ) / (X P-A ×M D )×100%, where M P M is the percentage of pigment mass in the oily color paste formula, D is the mass percentage of the effective dispersant in the oil-based color paste formula, then the dispersant adsorption efficiency E of the phthalocyanine blue pigment sample A effectively adsorbed by 100% effective dispersant is A =(X D-A ×M P ) / (X P-A ×M D )×100%=(12.57%×20%) / (87.43%×4%)×100%=71.89%; The dispersant adsorption efficiency E of the phthalocyanine blue pigment sample B with 100% effective dispersant adsorption is calculated by the same method. B , the calculation formula is E B =(X D-B ×M P ) / (X P-B ×M D )×100%, then the dispersant adsorption efficiency E of the phthalocyanine blue pigment sample B effectively adsorbed by 100% effective dispersant is B =(X D-B ×M P ) / (X P-B ×M D )×100%=(13.93%×20%) / (86.07%×4%)×100%=80.92%.
[0063] Test example: Phthalocyanine blue slurry sample particle size test
[0064] The particle size data of phthalocyanine blue paste sample A and phthalocyanine blue paste sample B were measured (particle size analyzer Malvern, Zetasizer Pro), and the results are shown in Table 2 below.
[0065] Table 2 Particle size data of phthalocyanine blue paste sample A and phthalocyanine blue paste sample B
[0066]
[0067]
[0068] From the comparison of the particle size data table in Table 2, it can be seen that the D10, D50, and D90 particle size data of phthalocyanine blue paste sample A are 85.75nm, 162.3nm, and 330.7nm, respectively, and the D10, D50, and D90 particle size data of phthalocyanine blue paste sample B are 69.37nm, 142.6nm, and 294.6nm, respectively, indicating that phthalocyanine blue paste sample B has a smaller particle size and particle size distribution range, so phthalocyanine blue paste sample B has a higher color paste dispersion. In contrast to the above test analysis of the dispersant adsorption efficiency in the phthalocyanine blue slurry sample, the dispersant adsorption efficiency of phthalocyanine blue slurry sample A is 71.89%, and the dispersant adsorption efficiency of phthalocyanine blue slurry sample B is 80.92%, indicating that the pigment particle surface of phthalocyanine blue slurry sample B adsorbs more dispersant, so it can provide a greater steric effect or charge effect to make the pigment particles repel each other, blocking the aggregation and flocculation caused by the van der Waals force between the pigment particles, so phthalocyanine blue slurry sample B has a smaller particle size performance and color paste dispersion. In summary, the method of the present invention applies thermogravimetric analysis to the field of color paste analysis technology, and quantitatively analyzes the adsorption efficiency of the dispersant in the color paste on the pigment surface by the difference in weight loss rate of the pigment and the dispersant in the color paste in the thermogravimetric analysis test. It is simple and effective, does not require a complicated sample preparation process, has a low instrument cost, can solve the problems existing in the prior art, fills the current research gap on the dispersant adsorption efficiency in the color paste, and provides theoretical guidance and data support for the formulation design and performance regulation of the color paste, which is of great significance to the application and development of the color paste in the fields of coatings, inks, plastics, cosmetics, etc.
[0069] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for analyzing the adsorption efficiency of a dispersant in an oily color paste, characterized in that: The following steps are involved: (1) using a thermogravimetric analyzer to perform thermogravimetric analysis on a 100% effective dispersant sample, a 100% effective pigment sample, and a 100% effective dispersant effectively adsorbed pigment sample to obtain thermogravimetric curves (TGA) of the three samples, and performing first-order differential data processing on the thermogravimetric curves (TGA) of the 100% effective dispersant sample and the 100% effective pigment sample to obtain differential thermogravimetric curves (DTG) of the 100% effective dispersant sample and the 100% effective pigment sample; (2) Determine the temperature at the intersection of the differential thermogravimetric curves of the 100% effective dispersant sample and the 100% effective pigment sample, and record it as the adsorption efficiency analysis temperature (T A ); 100% effective dispersant sample, 100% effective pigment sample, 100% effective dispersant effectively adsorbed pigment sample at adsorption efficiency analysis temperature (T A ) are recorded as W D , W P and W P-D ; (3) Based on the above data, calculate the proportion of dispersant in the pigment sample with 100% effective dispersant adsorption X D and pigment ratio X P , the calculation formula is X D =(W P-D -W P )÷(W D -W P )×100%,X P =(1-X D )×100%; (4) Based on the above data, the dispersant adsorption efficiency E in the pigment sample with 100% effective dispersant adsorption is calculated, and the calculation formula is E = (X D ×M P ) / (X P ×M D )×100%, wherein the M P M is the mass percentage of pigment in the oil-based color paste formula, D It is the mass percentage of the effective dispersant in the oily color paste formula.
2. The method for analyzing the adsorption efficiency of dispersants in oily color pastes according to claim 1, characterized in that: The preparation method of the 100% effective dispersant sample is as follows: The dispersant sample used in the oil-based color paste is dried to remove the organic solvent to obtain a dispersant sample with 100% effective content.
3. The method for analyzing the adsorption efficiency of dispersants in oily color pastes according to claim 1, characterized in that: The preparation method of the pigment sample with 100% effective content is as follows: The pigment used in the oil-based color paste is dried to remove the adsorbed solvent that may be contained, thereby obtaining a pigment sample with 100% effective content.
4. The method for analyzing the adsorption efficiency of dispersants in oily color pastes according to claim 1, characterized in that: The preparation method of the pigment sample effectively adsorbed by the dispersant with 100% effective content is as follows: The oily color paste sample is centrifuged, the solid obtained is collected and dispersed and washed with an organic solvent, and then centrifuged again, the solid obtained is collected and dried, and after removing the organic solvent, a pigment sample with 100% effective content of the dispersant effectively adsorbed is obtained.
5. The method for analyzing the adsorption efficiency of dispersants in oily color pastes according to claim 1, characterized in that: The test conditions of the thermogravimetric analysis test are as follows: Nitrogen or argon was selected as the protective gas, the test temperature range was set to 50°C-600°C or 50°C-800°C, the heating rate was set to 10-30°C / min, and the test sample weight was 0.5-5.0 mg.
6. The method for analyzing the adsorption efficiency of dispersants in oily color pastes according to claim 2, characterized in that: The drying process is carried out in an oven at 120° C. for 24 hours.
7. The method for analyzing the adsorption efficiency of dispersants in oily color paste according to claim 3, characterized in that: The drying process is carried out in an oven at 120° C. for 24 hours.
8. The method for analyzing the adsorption efficiency of dispersants in oily color pastes according to claim 4, characterized in that: Preferably, the preparation method of the pigment sample with 100% effective dispersant adsorption is as follows: (1) After the oily color paste sample is centrifuged at 15000 rpm for 30 min, the solid at the bottom is collected and dispersed and washed with an organic solvent; (2) The washed sample was centrifuged again at 15,000 rpm for 30 min to remove the unabsorbed dispersant and resin remaining on the surface, and the solid at the bottom was collected; (3) The collected solid is dried in an oven at 120° C. for 24 h to obtain a pigment sample in which 100% of the effective content of the dispersant is effectively adsorbed.
